Pengaruh Variasi Pelarut antara Amoniak dan Aquades terhadap Karakterisasi Difraksi Sinar-X Bahan SnO2 - Posman Manurung (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Synthesis has been done and characterization of X-ray diffraction (XRD) SnO2 materials produced by the precipitation process from starting materials with SnCl2 variation between ammonia and solvent aquades each one to one up to six. C for 4 hours Sintering temperature of the sample conducted at 1050. The results of qualitative analysis of the sample shows clearly the presence of SnO2 phase with tetragonal crystal structure and space group P42/MNM. The results of refining the XRD data using SnO2 sample Rietveld method between 1.52 to 4.08 2 produces the best matching score ( In general, all cell parameters length is the same sample. In comparison the variation of solvent 1:4, 1:5 and 1:6 high changes in the hkl diffraction peak (110) and (011) as a result of changes in grain size sample.Keywords: Tin Dioxide (SnO2), Presipitation, Rietveld Analysis